Agricultural Producers' Willingness to Pay for Real-Time Mesoscale Weather Information - Philip L. Kenkel; Patricia E. Norris (Journal of Agricultural and Resource Economics, 1995)
Mesoscale weather networks can provide improved weather information to agricultural producers. This technology can potentially improve production decisions, reduce irrigation and pesticide inputs, and reduce weather-related losses. Developing a mesoscale network to disseminate real-time mesoscale weather information requires a substantial investment. In addition, there are costs associated with maintenance of the system and distribution of the information available. While public funds may be available to support initial development of the system, there may be less public support initial development of the system, there may be less public support for maintaining the system and subsidizing users' access to the information. This study uses the contingent valuation technique to determine the willingness of Oklahoma farmers and ranchers, as one set of potential users, to pay for real-time mesoscale weather information. The results indicate that agricultural producers are willing to pay only a modest fee for improved weather information. Gross sales, irrigation, and past weather losses are among the factors shown to significantly impact willingness to pay.